EVALI versus MIS‐C, one more overlapping diagnosis to consider. Issue 9 (16th July 2021) - Cruz‐Vidal, Diego A.; Mull, Eric S.; Taveras, Jeanette; Shell, Richard; Hunt, Garrett W.; Fowler, Brian; Wallihan, Rebecca; Erdem, Guliz
Abstract: We describe six teenagers presenting with fever and severe abdominal symptoms admitted with concerns for multisystem inflammatory syndrome in children (MIS‐C). Laboratory evaluation revealed elevated markers of inflammation, lymphopenia, and increased D‐dimers. Imaging studies revealed multifocal airspace disease and ground‐glass opacities. SARS‐CoV‐2 polymerase chain reaction and serologies were negative. All patients reported a history of vaping, prompting E‐cigarette, or vaping, product use‐associated lung injury (EVALI) diagnosis. MIS‐C has overlapping clinical and laboratory features highlighting the added challenge of diagnosing EVALI during the COVID‐19 pandemic. Keywords COVID‐19 pandemic, EVALI, MIS‐C